Since the instruction, R_{2} + 2 R_{1}, is written next to the second row, we must replace the second (bottom) row by the bottom row + twice top row.

Now, rewrite the second row, going from left to right, as follows:

**First entry: **

- (bottom) + 2(top) = -1 + 2(-2) = -1 - 4 = -5.

Therefore, the first entry is -3.

**Second entry:**

- (bottom) + 2(top) = 1 + 2(-2) = 1 - 4 = -3.

This is the second entry.

**Third entry:**

- (bottom) + 2(top) = 3 + 2(0) = 3 + 0 = 3.

Thus, the new bottom row is

- [-5 -3 3].

Close this window to return to the tutorial.